LED SCANNING MATRIX USING PPI 8255 - Indrianto Indrianto; Ir. Irwan Nimara, MMSI (Jurnal Sistem Komputer, 1998)
In order to connect a PC to the outside world, needed a tool called Interface. Interface in this case serves as a door exit and entry information digitally to the procedures and capabilities tailored to the program. So to use it requires a special program. In designing an interface must be determined beforehand in the memory area where these interfaces can work well and do not interfere with other peripherals. This is intended so that if later on that interface will be installed into the computer will not change the working procedures of the computer in general.